PENGARUH SENI PERTUNJUKAN TERHADAP TINGKAT KUNJUNGAN DI DAYA TARIK WISATA BUDAYA TAMAN NUSA GIANYAR - BALI - Made Darmiati (JURNAL KEPARIWISATAAN, 2020)
This study aims to determine the influence of performing arts to the level of tourist visits in the Park Nusa Gianyar Bali. The results showed (1) that there was a real positive effect between Barong dance performances (X1) individually to visit in Taman Nusa (Y). (2) that there is a real positive influence between the performing arts of Angklung instrument (X2) individually to visit in Taman Nusa (Y). (3) that there is a real positive influence between dance performances of the archipelago (X3) individually to visit in Taman Nusa (Y). Can be concluded that the performing arts as a tourism product of PT. Taman Nusa, has a strong or very significant influence on the level of tourist visits to Taman Nusa. So that PT. Taman Nusa to be able to develop new innovations relating to the performing arts as a great potential in tourism products owned.